Enhancing Educational Comic Book Innovation Through Design Thinking: A Case Study of Lab Buddy - Chairunnisa, Ainaya; Suharto, Yulianto (Journal Integration of Social Studies and Business Development, 2024)
Indonesia's significant demographic dividend presents a valuable opportunity that should be leveraged to achieve the vision of Indonesia Emas 2045, with a key focus on enhancing educational quality. Despite government efforts to increase the number of schools, the quality of education in Indonesia still lags behind international standards. To address this issue, the Indonesian government needs to develop a learning environment that caters to students' diverse needs and learning styles, particularly in Mathematics. Technological advancements have introduced innovative educational tools, including math educational comics. This research aims to develop an innovative math educational comic that aligns with students' and parents' needs and preferences, utilizing the design thinking approach. Data was collected through semi-structured interviews with the target customers of this product—the analysis of this data involved open coding, pattern coding, and triangulation to ensure validity. The findings indicate that while the product aligns with the respondents' needs and preferences, there is room for improvement in the comic's sentence structure. Feedback from participants should be carefully considered before finalizing the product, underscoring the importance of design thinking in effectively addressing the needs and preferences of the target audience.